2005
DOI: 10.1016/j.neuron.2005.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Organization of Tone Sequences in the Auditory Cortex of Awake Macaques

Abstract: Acoustic sequences such as speech and music are generally perceived as coherent auditory "streams," which can be individually attended to and followed over time. Although the psychophysical stimulus parameters governing this "auditory streaming" are well established, the brain mechanisms underlying the formation of auditory streams remain largely unknown. In particular, an essential feature of the phenomenon, which corresponds to the fact that the segregation of sounds into streams typically takes several seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
391
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(443 citation statements)
references
References 52 publications
48
391
4
Order By: Relevance
“…Using MEG, they showed an increased response suggestive of reduced forward suppression when two streams were perceived. Similarly, the EEG study of Snyder et al (2006) found correlates of the build-up of streaming (i.e., the increased tendency to hear two streams with increased time of exposure to the stimuli) in auditory cortex as did Micheyl et al (2005) in their analysis of single-unit activity in monkey primary auditory cortex. One possibility that partly reconciles the existing data are as follows: In the case of bistable tone sequences, the conscious perception of distinct streams may be mediated directly by a small subset of temporally synchronized neurons whose activity in fMRI is swamped by contributions from other, unsynchronized neurons, but is detectable in MEG and EEG because of the sensitivity of these techniques to temporally synchronous neural activity.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Using MEG, they showed an increased response suggestive of reduced forward suppression when two streams were perceived. Similarly, the EEG study of Snyder et al (2006) found correlates of the build-up of streaming (i.e., the increased tendency to hear two streams with increased time of exposure to the stimuli) in auditory cortex as did Micheyl et al (2005) in their analysis of single-unit activity in monkey primary auditory cortex. One possibility that partly reconciles the existing data are as follows: In the case of bistable tone sequences, the conscious perception of distinct streams may be mediated directly by a small subset of temporally synchronized neurons whose activity in fMRI is swamped by contributions from other, unsynchronized neurons, but is detectable in MEG and EEG because of the sensitivity of these techniques to temporally synchronous neural activity.…”
Section: Discussionmentioning
confidence: 74%
“…The present findings indicate a more broadly distributed sensitivity to f 0 that may reflect neuronal sensitivity to the differing temporal properties of tones of different f 0 , rather than a sensitivity to pitch per se. Frequency-selective forward suppression of neural responses in the auditory cortex (or the equivalent in nonmammalian species) has been proposed to play an essential role in auditory streaming (Fishman et al, 2001(Fishman et al, , 2004Kanwal et al, 2003;Klump, 2004, 2005;Micheyl et al, 2005Micheyl et al, , 2007. Specifically, it has been suggested that whether a sequence of pure tones is perceived as a single coherent stream or as two separate streams depends on the degree to which one tone influences the responses to subsequent tones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal electrophysiology, build up provides a useful tool for accessing the temporal dynamics of streaming, as it is a measure that can be averaged across trials and that does not require the co-registration of the perceptual state. Correlates of build up have been found both in the auditory cortex [14] and in the cochlear nucleus [15] of the mammalian auditory system. Interestingly, in all of the published data, after the initial build up, the probability of hearing two streams stabilizes below 100%.…”
Section: Introductionmentioning
confidence: 99%
“…The primary auditory cortex thus seems to be a good candidate for at least the first step in auditory stream segregation; see (Fishman et al, 2001;Micheyl et al, 2005) for some experimental evidence.…”
Section: Sound Discrimination In Freely Moving and Head-fixed Ratsmentioning
confidence: 99%